Mob queen - Bledsoe, Erin (Blackstone Publishing, 2025)
Virginia Hill escaped her abusive father by marrying a man who took her to Chicago, only to end up divorced and destitute. Virginia joins her new friend Madeline working as a waitress in one of the Mob's favorite hangouts. When Madeline disappears after getting involved with the wrong Mafia man, Virginia vows to find her friend no matter what. But to do that, she'll have to follow Madeline into the heart of the Chicago Mob.